Financial crisis, fiqh Muamalat and international commutative transactions: an empirical assessment of the value of contemporary currency in light of the prohibition against Gharar - Witbrodt, Matthew; Rohimi Shapiee (Penerbit Universiti Kebangsaan Malaysia, 2013)
Financial crises are common facets of the contemporary economic environment. The present study examines the effects of the 1997 Asian Financial Crisis on the value of the Indonesian Rupiah (IDR) against the US Dollar (USD) over a 186-month period, including the 12-month period prior to the formal beginning of the financial crisis; the 18-month period of the financial crisis; and a 156-month period following the financial crisis, during which the continuing effects of the value crisis accompanying the financial crisis are observed. The principle objective of the present study is to empirically measure the level of uncertainty concerning the value of the IDR against the USD and the effects of the uncertainty on the Shariah compliance of international commutative transactions during and following the financial crisis, taking the form of either spot exchanges or exchanges involving deferred payments, in relation to the prohibition against gharar. Premised upon purchasing power parity theory, the present study examines the exchange rate based upon the perceived local value of the two currencies, measured as the real exchange rate (RER) based upon inflation data for the two currencies; and the perceived value of the Indonesia Rupiah according to international financial markets, measured by the nominal exchange rate (NER) between the two currencies. The purchasing power parity between the NER and RER is then examined to determine a gharar threshold that determines whether the disparity between the two values constitutes a minor level of uncertainty, which is permissible under Shariah law, or excessive uncertainty, which is forbidden in commutative transactions under Shariah law. Based upon the gharar threshold determined, the conclusion and/or completion of international commutative transactions during and following the financial crisis (until the resolution of the value crisis) are deemed to include excessive uncertainty, raising serious doubts concerning the validity of such transactions under Shariah law.